Left atrial effective conducting size predicts atrial fibrillation vulnerability in persistent but not paroxysmal atrial fibrillation. (18th June 2019) - Williams, Steven E.; O'Neill, Louisa; Roney, Caroline H.; Julia, Justo; Metzner, Andreas; Reißmann, Bruno; Mukherjee, Rahul K.; Sim, Iain; Whitaker, John; Wright, Matthew; Niederer, Steven; Sohns, Christian; et al.
Abstract: Background: The multiple wavelets and functional re‐entry hypotheses are mechanistic theories to explain atrial fibrillation (AF). If valid, a chamber's ability to support AF should depend upon the left atrial size, conduction velocity (CV), and refractoriness. Measurement of these parameters could provide a new therapeutic target for AF. We investigated the relationship between left atrial effective conducting size (LAECS ), a function of area, CV and refractoriness, and AF vulnerability in patients undergoing AF ablation. Methods and Results: Activation mapping was performed in patients with paroxysmal (n = 21) and persistent AF (n = 18) undergoing pulmonary vein isolation. Parameters used for calculating LAECS were: (a) left atrial body area ( A ); (b) effective refractory period (ERP); and (c) total activation time ( T ). Global CV was estimated as √ A / T . Effective atrial conducting size was calculated as LA ECS = A / ( CV × ERP ) . Post ablation, AF inducibility testing was performed. The critical LAECS required for multiple wavelet termination was determined from computational modeling. LAECS was greater in patients with persistent vs paroxysmal AF (4.4 ± 2.0 cm vs 3.2 ± 1.4 cm; P  = .049). AF was inducible in 14/39 patients. LAECS was greater in AF‐inducible patients (4.4 ± 1.8 cm vs 3.3 ± 1.7 cm; P  = .035, respectively). The difference in LAECS between inducible and noninducible patients was significant in patients with persistent ( P  = .0046) but not paroxysmal AF ( P  = .6359). Computational modeling confirmed that LAECS  > 4 cm was required for continuation of AF. Conclusions: LAECS measured post ablation was associated with AF inducibility in patients with persistent, but not paroxysmal AF. These data support a role for this method in electrical substrate assessment in AF patients.